State of the art in negotiation ontologies for multi-agent systems - Dong, Hai; Hussain, Farookh Khadeer; Chang, Elizabeth (Web Services Research Foundation, 2008)
In a multi-agent system, a business may start by two agents that have the desire of trading, in which negotiation is an inevitable procedure for building the business relationship. In the context of e-business, agents that represent humans have the potential ability to commence automated negotiation activities. Traditional negotiation research focuses on providing approaches for generating negotiation strategies and protocols to realize the ability of agents. However, there are some issues in this field - the inadaptability of agents to evolving negotiation protocols, and agents' negotiation term ambiguity. Ontology is a semantic web technology for defining domain knowledge and solving semantic ambiguity, which can be extended into the field of automated negotiation research. In this paper, we attempt to make a survey to the existing negotiation ontologies, and explore the current status of the negotiation ontology research.